Structural Design of Multi-Functional Building - عبد العزيز الخراز; احمد سمير; مجد سلامة; اكريم بشناق (My University, 2023)
Reinforced concrete structures are one of the most popular structural systems used in Palestine. This project is about the structural design of a new Multi-functional building in Nablus city, Sham building one. This building consists of 15 Stores, with plan area 290.787m2. This project will be divided into two parts. The first part intends to prepare the basic information required to facilitate efficient modeling and structural design and analysis of the building under static loads. The design of concrete elements is controlled by ACI 318-19 code. The second phase will be redesign of building considering gravity as well as seismic loads. This design will be based on IBC - 19. Structural elements such as footings, stairs, columns, beams, slabs and shear walls will be completed and finalized in part two. To make a mathematical model that represents the reality, 3-D structural model will be made using ETABS 2016 program. The analysis is verified using conceptual hand calculation for sample output from the program. Detailed design of all structural elements for gravity and seismic loads will be done and drawn using AutoCAD program.